Adverse events associated with vismodegib: insights from a real-world pharmacovigilance study using the FAERS database - Wang, Bingqing; Zhao, Kaidi; Xian, Ningyi; Ren, Landong; Liu, Jiashu; Tu, Chen; Zhang, Dewu (Frontiers in Pharmacology, 2025)
BackgroundVismodegib, an inhibitor of the Hedgehog signaling pathway, has been widely used in the treatment of advanced basal cell carcinoma. Given its critical role in managing advanced basal cell carcinoma and the relatively high rate of treatment discontinuation, it is crucial to comprehensively understand its safety profile in real-world settings.MethodsThis study analyzed all adverse event reports that identified vismodegib as the primary suspected drug since 2012 in the FDA Adverse Event Reporting System database. Disproportionality analysis was conducted using four algorithms: Reporting odds ratio, proportional reporting ratio, multi-item gamma Poisson shrinker, and Bayesian confidence propagation neural network to assess the safety profile of vismodegib in clinical practice. Additionally, this study employed the Weibull distribution to model the risk of adverse events over time.ResultsA total of 7,733 adverse event reports associated with vismodegib were identified from the FDA Adverse Event Reporting System database. Data mining identified positive signals for on-label adverse events, such as muscle spasms, taste alterations, alopecia, fatigue, and weight decreased. Notably, potential off-label adverse events including squamous cell carcinoma, dehydration and dysphagia were also detected. The median time to onset for these adverse events was 69 days post-drug administration, highlighting the importance of close monitoring, particularly within the initial 2 months of treatment.ConclusionThis study provides valuable insights into the real-world safety profile of vismodegib. It not only confirms the known adverse events on the label, but also suggests several potential novel adverse events, thereby supporting a more informed and rational use of vismodegib in clinical practice.